A Prospective Randomized Study on the Immediate Loading of Mandibular Overdentures Supported by One or Two Implants; A 3 Year Follow‐Up Report. (21st September 2012) - Kronstrom, Mats; Davis, Ben; Loney, Robert; Gerrow, Jack; Hollender, Lars
Abstract Aim The objective of the study was to evaluate and compare treatments with mandibular overdentures supported by one or two immediately placed implants 3 years after loading. Materials and Methods Thirty‐six edentulous subjects were eligible for inclusion. Using a random sampling system, one or two implants were placed in the mandible. Separate ball attachments were connected to the implants, and the denture was relined and delivered the day of surgery with the retentive components incorporated in the denture base. At the follow‐up examinations peri‐implant bone levels, implant and denture stability/retention, and need for maintenance and adjustments were evaluated. Moreover, the OHIP‐EDENT questionnaire was used to measure patient satisfaction. Results Nineteen subjects (10 men and 9 women) with a mean age of 56 years were available for the 3‐year follow‐up examination. The group with 1 implant (Group 1) consisted of 11 subjects (5 women and 6 men) while the remaining 8 (5 women and 3 men) belonged to Group2. Nine subjects had been excluded during the first year due to failing implants, 6 had moved, 1 had died, and 1 reported severe illness. No implant failures between the 12‐and 36 month follow‐up were observed. The mean peri‐implant bone change was.86 mm and the Implant Stability Quotient showed only minor changes with no significant difference between the groups when compared with the 12‐month follow‐up. Patient satisfaction scores increased significantly when compared with the baseline values and continued to be high for both groups and need for denture maintenance was low. Conclusion No significant differences were found between subjects in the two groups with respect to implant survival and peri implant bone loss, and patient satisfaction scores continued to be high for both groups. Need for denture maintenance was low in both groups.